An easily fabricated palladium nanocatalyst on magnetic biochar for Suzuki–Miyaura and aryl halide cyanation reactions. (29th June 2021) - Turunç, Ersan; Akay, Sema; Baran, Talat; Kalderis, Dimitrios; Tsubota, Toshiki; Kayan, Berkant
Abstract : A sustainable biochar material for the synthesis of a novel heterogeneous catalyst for organic reactions is reported. Abstract : Biochar is a carbon-rich solid, the surface of which is covered with a high density of functional carbonyl, hydroxyl and carboxylic acid groups. In this work, palladium nanoparticles were embedded on magnetic biochar and a new reusable and environmentally-friendly catalyst was developed and applied for the promotion of Suzuki–Miyaura C–C coupling and cyanation reactions. The high-carbon (77%), low-ash content (5.8%) and the relatively high surface area (266 m 2 g −1 ) of pine tree biochar (PTB) suggested that it might be highly suitable as a catalyst substrate. The Fe3 O4 -Pd–biochar nanocomposite was successfully characterized using SEM, TEM, EDX, FT-IR, BET and XRD. Its catalytic role was initially evaluated using p -NO2 C6 H4 I as a model reactant (for both types of reactions) and later for the production of biaryls and benzonitriles from a wide range of aryl halides under mild reaction conditions. Biaryls and benzonitriles were characterized using GC-MS. In the case of the Suzuki–Miyaura reaction, the optimum yield of 98% was obtained with a catalyst concentration of 0.04 mol%, microwave irradiation of 400 W, and a residence time of 5 min, using K2 CO3 as the base. With respect to the cyanation reaction, dimethylformamide, Na2 CO3 and 6 h were the optimum solvent, base and reaction duration, respectively. Subsequently, the nanocatalyst showed excellent catalytic activity in both reactions, achieving >88% yields in most cases, regardless of the aryl iodide or bromide used and the type of substitution.